2023
DOI: 10.1038/s41467-023-37164-x
|View full text |Cite
|
Sign up to set email alerts
|

The core metabolome and root exudation dynamics of three phylogenetically distinct plant species

Abstract: Root exudates are plant-derived, exported metabolites likely shaping root-associated microbiomes by acting as nutrients and signals. However, root exudation dynamics are unclear and thus also, if changes in exudation are reflected in changes in microbiome structure. Here, we assess commonalities and differences between exudates of different plant species, diurnal exudation dynamics, as well as the accompanying methodological aspects of exudate sampling. We find that exudates should be collected for hours rathe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…For root organic acid exudates analysis, two maize plants from each plastic container having uniform size were cautiously uprooted, cleansed with ddH 2 O, and transferred to the rhizobox system for organic acid collection (Figure S1; McLaughlin et al, 2023). The rhizobox system comprised a nylon net (25 mm) enveloped around plant roots and 200-g autoclaved moist soil.…”
Section: Analysis Of Root Exudatesmentioning
confidence: 99%
“…For root organic acid exudates analysis, two maize plants from each plastic container having uniform size were cautiously uprooted, cleansed with ddH 2 O, and transferred to the rhizobox system for organic acid collection (Figure S1; McLaughlin et al, 2023). The rhizobox system comprised a nylon net (25 mm) enveloped around plant roots and 200-g autoclaved moist soil.…”
Section: Analysis Of Root Exudatesmentioning
confidence: 99%
“…In addition, there is evidence that specific compounds associated with more specialized plant–microbe interactions, such as triterpenes and benzoxazinoids, are exuded by Arabidopsis and grasses, respectively (Hu et al ., 2018; Huang et al ., 2019). Root exudate metabolite profiles of A. thaliana , Brachypodium distachyon , and Medicago truncatula showed significant differences among different species (Brecht et al ., 2022). Microbiome composition and root exudates varies with plant developmental stage (Aulakh et al ., 2001; Bulgarelli et al ., 2013), for example, in Arabidopsis , altered triterpene exudation changed microbiome composition (Huang et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a strong phylogenetic signal in plant-soil feedback, while metabolic convergence was observed in aerial plant parts in response to abiotic threats (35,38,65,66). However, root and root exudate metabolic profiles tend to present less variation between species when compared to aerial plant parts (15). Here, while certain markers differed between vegetation belts ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, recent efforts improved our understanding of some biochemical mechanisms used by plants to interact with the microbial community (26). Nevertheless, it is reasonable to say that a significant portion of rhizosphere chemicals remains to be discovered and that little is known about how these signals shape the surrounding microbe community (15,18,27). Moreover, most studies were performed on single species.…”
Section: Introductionmentioning
confidence: 99%